Structural Advances in Voltage-Gated Sodium Channels - Jiang, Daohua; Zhang, Jiangtao; Xia, Zhanyi (Frontiers in Pharmacology, 2022)
Voltage-gated sodium (NaV) channels are responsible for the rapid rising-phase of action potentials in excitable cells. Over 1,000 mutations in NaV channels are associated with human diseases including epilepsy, periodic paralysis, arrhythmias and pain disorders. Natural toxins and clinically-used small-molecule drugs bind to NaV channels and modulate their functions. Recent advances from cryo-electron microscopy (cryo-EM) structures of NaV channels reveal invaluable insights into the architecture, activation, fast inactivation, electromechanical coupling, ligand modulation and pharmacology of eukaryotic NaV channels. These structural analyses not only demonstrate molecular mechanisms for NaV channel structure and function, but also provide atomic level templates for rational development of potential subtype-selective therapeutics. In this review, we summarize recent structural advances of eukaryotic NaV channels, highlighting the structural features of eukaryotic NaV channels as well as distinct modulation mechanisms by a wide range of modulators from natural toxins to synthetic small-molecules.